POTENSI ANCAMAN INVASIF IKAN OSKAR (Amphilophus citrinellus) DI WADUK IR. H. DJUANDA, JAWA BARAT - Prawira Atmaja; R. P. Tampubolon; M. F. Rahardjo; Krismono Krismono (Widyariset, 2014)
The alien species phenomenon is one of the greatest concerns in environmental issue. This research was held since October 2011 until Januari 2012 in Ir. H. Djuanda Reservoir, West Java. The study aims to describe the potential of Amphilophus citrinellus threatening invasion in Ir. H. Djuanda Reservoir referring to its ecobiological aspects. Total number of fish caught during research period was 657 fish. Six of 12 species caught were indigenous species. Midas cichlid dominated the amount of fish caught, with total length and weight ranging between 62–210 mm and 4.81–187.18 gram, respectively. It had adapted well and not only survived and grown in somatic but also grown in gonadic without being affected by season change. This fish is omnivore and usually consumes all sources of food within the feeding area. Other fish species thought to be utilized in the same way with the small, medium, and the large-sized Midas Cichlid is Barbonymus balleroides. This fish is an invasive potential for this particular region and controlling its population is a must.